2019
DOI: 10.1136/bmjresp-2018-000373
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of ambulatory management of secondary spontaneous pneumothorax: a case series

Abstract: IntroductionThe optimal management of pneumothorax remains undefined. There is a growing consensus that patients with spontaneous pneumothorax can be considered for ambulatory management with the use of a one-way valve. Despite this, there is little data on the outcomes of outpatient management of secondary spontaneous pneumothorax (SSP).MethodsAt our institution, selected patients with primary and secondary spontaneous pneumothorax who meet the predefined local criteria are managed on an ambulatory pathway. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The review cited high rates of success in patients with SSP, defined as use of a flutter valve with a chest tube to manage pneumothorax. A subsequently published prospective case series of a selected cohort of patients with SSP reported that 65% (32/49) were successfully managed with the AP attached to a 12F chest drain [12]. However, non-randomised case-series are subject to high risk of selection bias, with sick and complex patients at greater risk of exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The review cited high rates of success in patients with SSP, defined as use of a flutter valve with a chest tube to manage pneumothorax. A subsequently published prospective case series of a selected cohort of patients with SSP reported that 65% (32/49) were successfully managed with the AP attached to a 12F chest drain [12]. However, non-randomised case-series are subject to high risk of selection bias, with sick and complex patients at greater risk of exclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The one study had a success rate of 79% in patients with large pneumothoraces and 37% had full outpatient management, [46] while the other study found that ambulatory management can be effective even in patients with overt underlying lung disease with a mean drainage time of 5.84 days. [47] Both studies found that this method was associated with reduced hospital costs and avoided potential tension pneumothoraces. In a situation where a patient has ready access to transport and is close to the treating healthcare facility, ambulatory management may be an appropriate strategy.…”
Section: Management Of a Spontaneous Pneumothoraxmentioning
confidence: 99%
“…A large bore chest tube drainage and regular inpatient admission are becoming less of the primary strategies for treating primary spontaneous pneumothorax (PSP). Therefore, the current controversy centers on three competing evidence-based options for ambulatory management of large pneumothoraces: watchful waiting (20,22,23) vs. 16-gaude (G) needle aspiration (7)(8)(9)(10)(12)(13)(14)(15)(16) vs. thoracic vent with an 8-11 French tube (21,(24)(25)(26)(27)(28). These reports indication are mainly for PSP, but other pneumothorax is well unknown.…”
Section: Original Articlementioning
confidence: 99%